PENYADAPAN GETAH PINUS MERKUSII DENGAN MENGGUNAKAN BEBERAPA POLA SADAP DAN TINGKAT KONSENTRASI ZAT PERANGSANG - Ishak Sumantri; Wesman Endom (Jurnal Penelitian Hasil Hutan, 1989)
Three  methode for  tapping pine tree resin.  i.e.,   3 x 4  cm,  1,5 x8 cm and Indian  tapping  method   were investigated  in Cianjur Forest  District  in  1988.   To  increase  the  resin yield,  sulphuric  acid  (H2S04)   with  0%, 15  %, 25 %, and 35 % con- cetratation   were  used.  Each  tapping  method   was applied  on  fourty   pine  trees.  The  results  are as fallows  :1.Using stimulant   with  the  three  methods   of  tapping  increase  the  resin yield.               2.From   the.  three   tapping   methods   applied,   Indian   tapping  method   showed   the  highest  resin  yield,    i.e.   12. 72 gram/tree/day.3.Indian   tapping   method   gives  Rp  5/kg  profit.   This  value  was found   by  subtracting   selling  price  (Rp,   150/kg)   with production  cost  (Rp.   145/kg).